Religion and Spirituality among American Indian, South Asian, Black, Hispanic/Latina, and White Women in the Study on Stress, Spirituality, and Health. Issue 1 (22nd December 2020) - Kent, Blake Victor; Davidson, James C.; Zhang, Ying; Pargament, Kenneth I.; VanderWeele, Tyler J.; Koenig, Harold G.; Underwood, Lynn G.; Krause, Neal; Kanaya, Alka M.; Tworoger, Shelley S.; Schachter, Anna B.; Cole, Shelley A.; et al.
Abstract: Social scientists have increasingly recognized the lack of diversity in survey research on American religion, resulting in a dearth of data on religion and spirituality (R/S) in understudied racial and ethnic groups. At the same time, epidemiological studies have increasingly diversified their racial and ethnic representation, but have collected few R/S measures to date. With a particular focus on American Indian and South Asian women (in addition to Blacks, Hispanic/Latinas, and white women), this study introduces a new effort among religion and epidemiology researchers, the Study on Stress, Spirituality, and Health. This multicohort study provides some of the first estimates of R/S beliefs and practices among American Indians and U.S. South Asians, and offers new insight into salient beliefs and practices of diverse racial/ethnic and religious communities.